FAIR – Cosmic matter in the laboratory1. Issue 6 (August 2014) - Stoecker, H.; Sturm, C.
Abstract To explore cosmic matter in the laboratory – this fascinating research prospect becomes available in 2018 at the Facility for Antiproton and Ion Research, FAIR. The new facility is being constructed within the next five years adjacent to the existing accelerator complex of the GSI Helmholtz Centre for Heavy Ion Research at Darmstadt/Germany, expanding the research goals and technical possibilities substantially. This includes new insights into the dynamics of supernovae depending on the properties of short‐lived neutron‐rich nuclei which will be investigated with intense rare isotope beams. New insights will be provided into the interior of stars by exploring dense plasmas with intense heavy‐ion beams combined with a high‐performance laser – or into neutron star cores by probing the highest baryon densities in relativistic nucleusnucleus collisions at unprecedented collision rates. To the latter, the properties of hadrons play an important part which will be systematically studied by high precision hadron spectroscopy with antiproton beams at unmatched intensities. The worldwide unique accelerator and experimental facilities of FAIR will open the way for a broad spectrum of unprecedented fore‐front research supplying a large variety of experiments in hadron, nuclear, atomic and plasma physics as well as biomedical and material science which will be briefly described in this article. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)